The effects of benzo[a]pyrene on the composition of gut microbiota and the gut health of the juvenile sea cucumber Apostichopus japonicus Selenka. Issue 93 (October 2019) - Zhao, Ye; Liu, Hui; Wang, Qing; Li, Bingjun; Zhang, Hongxia; Pi, Yongrui
Abstract: The gut microbiota is essential for health and physiological functions in the host organism. However, the toxicological evaluation of environmental pollutants on the gut microbiota is still insufficient. In the present study, the juvenile sea cucumber Apostichopus japonicus was exposed for 14 days to Benzo[ a ]pyrene (BaP), which is a model polycyclic aromatic hydrocarbon (PAH), at four different concentrations (0, 0.5, 5, and 25 μg/L). We analyzed the intestinal microbial community of A. japonicas using 16S rRNA gene amplicon sequencing. Our results demonstrate that BaP exposure caused alterations to the microbiome community composition in sea cucumbers. At the phylum level, Planctomycetes were significantly more abundant in BaP exposure groups at 14 d compared with the control group, and the abundance of Proteobacteria and Bacteroidetes increased while the abundance of Firmicutes decreased following BaP exposure. At the genus level, multiple beneficial and autochthonous genera declined in the BaP treatment groups compared to the control, including Lactococcus, Bacillus, Lactobacillus, Enterococcus, Leuconostoc and Weissella ; however, a bloom of alkane-degrading bacteria was found in BaP-exposed guts and included Lutibacter, Pseudoalteromonas, Polaribacter, Rhodopirellula and Blastopirellula . Furthermore, histological morphology, enzymatic activity and gene expression analysis revealed that BaP exposure also negatively impacted gut structure and function and presented as inflammation or atrophy, oxidative stress and immune suppression in sea cucumber intestines. Collectively, these findings provide insights into the toxic effects of BaP exposure on A. japonicas associated with intestinal microbiota and health. Highlights: BaP exposure negatively impacted histological structure of gut in A. japonicas . BaP exposure led to antioxidant response and immune suppression in sea cucumbers. Microbiota structure in the gut of A. japonicus could be shaped by BaP exposure.